Clinical Presentation, Patient Assessment, Anatomy, Pathophysiology, and Imaging of Pelvic Venous Disease - Maratto, Sean; Khilnani, Neil M.; Winokur, Ronald S. (Seminars in Interventional Radiology, 2021)
Pelvic venous disorders (PeVDs) can result in several different clinical presentations, but can be challenging to distinguish from other etiologies of chronic pelvic pain (CPP). Clinical evaluation of CPP patients optimally should be performed in a multidisciplinary fashion and patients who may have PeVD should be referred for consultation with a vascular interventionalist whose evaluation would utilize an imaging workup to search for pelvic varices. Additionally, it is critical to quantify the quality-of-life effects of all CPP to determine the impact on the patient's overall health. Diagnostic imaging, including transabdominal and transvaginal ultrasound, computed tomography, magnetic resonance imaging, and venography, can be utilized to identify pelvic varices, as well as venous reflux and obstruction leading to CPP. The use of the SVP tool is important to classify PeVD patients based on their clinical symptoms, varicose veins, and pathophysiology for precise clinical communication and for reporting clinical research. The goal of this publication is to delineate the clinical presentation, anatomy, pathophysiology, and imaging evaluation of patients with CPP suspected of having PeVD.
Keywords: pelvic venous disease; pelvic congestion; diagnostic imaging; interventional radiology